2001
DOI: 10.1590/s0004-282x2001000300013
|View full text |Cite
|
Sign up to set email alerts
|

Determinação volumetrica do infarto cerebral na fase aguda usando tomografia computadorizada de crânio sem contraste: estudo comparando três métodos

Abstract: RESUMO -A determinação volumétrica do infarto cerebral agudo (IC) tem importantes implicações prognósticas e terapêuticas. Foram estudadas e comparadas três técnicas de determinação do volume do IC agudo (técnica computadorizada, planimetria linear e fórmula A.B.C/2) em 27 doentes usando imagens de TC sem contraste realizadas à internação (primeiras 48 horas de evolução). As aferições foram feitas por dois observadores independentes, sendo determinado o coeficiente de correlação intraclasse (CCI). Os três méto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Third, we did not analyze the therapeutic value of ABC/2 method. Some previous papers have shown the clinical value of infarct volume determined with the ABC/2 method in clinical decision making in acute settings 16–18 . These authors suggested that errors in estimating the volume of small infarcts have little impact on clinical decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we did not analyze the therapeutic value of ABC/2 method. Some previous papers have shown the clinical value of infarct volume determined with the ABC/2 method in clinical decision making in acute settings 16–18 . These authors suggested that errors in estimating the volume of small infarcts have little impact on clinical decision.…”
Section: Discussionmentioning
confidence: 99%
“…The ABC/2 is a fast volumetric method based on the formula of the ellipse; 15 it has been validated for hematoma management 15 but not for acute ischemic stroke 16,17 . Some publications 14,18 discuss the validity of ABC/2 for assessing acute infarct volume with respect to other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Infarct volume was evaluated in follow-up CT (computed tomography) scans performed 24–48 h after stroke by an experienced neurologist, blinded to clinical information, angiogenin levels, and cell populations of interest. Infarct volume was measured according to the formula AxBxC/2, where A and B represent the largest perpendicular diameters through the hypodense area on CT scan, and C represents the thickness of the infarct ( 30 ).…”
Section: Methodsmentioning
confidence: 99%